11- ONLAY MESH IN THE MANAGEMNT OF LARGE OR COMPLEX INCISIONAL HERNIA (Basrah Journal of Surgery, 2008)
The aim of this study is to evaluate the use of onlay mesh in the management of large or complex incisional hernia. A prospective study of 80 patients with incisional hernia operated on at al-Sadr Teaching Hospital treated with onlay mesh between Jan 2001 to Jan 2006. Thorough history and physical examination was done, data sheet was designed include numerous factors that effect operative and healing process. Of 80 patients, 61.2% female &38.8 % male with median age 40.1 years for female & 53 years for male. Patients were with different associated medical problems. Main incision was lower midline incision 26.2% &main post operative complications was seroma 7.5% & wound infection 7.5% while recurrence of hernia observed in 2.5%.This study showed that, the big incisional hernias can be efficiently treated by the onlay positioning of polypropylene mesh.